Seasonal concentration of cruise tourism in the Mediterranean - Cisneros-Martínez, José David; Fernández-Morales, Antonio (My University, 2016)
This research delves into analyzing the seasonality of cruise tourism in the Mediterranean by using the decomposition of the Gini index, used in the field of cruise tourism for the first time in literature. This study specifically used the decomposition to evaluate the contribution degree of each port to the global seasonal concentration of each Mediterranean region. Moreover, a cluster analysis technique (bootstrapped bagged clustering) was applied to classify the ports into homogeneous groups according to their seasonal patterns given the significant heterogeneity revealed in the major regions of the Mediterranean. The methodology applied can serve as a control and monitoring tool for measuring seasonal concentration levels in cruise tourism, allowing for policies against seasonality to be tailored in the cruise tourism segment.
Keywords: Turismo; Seasonality; Bagged cluster analysis; Gini index; Cruise tourism